Senkatana - Mofokeng, ...,Mahase, ... (Wits University Press, 2021)
Senkatana is a Sesotho play based on a Basotho legend about a monster that swallowed all the people and animals except for one pregnant woman. She gave birth to a boy, Senkatana, when a young man, killed the monster. The grateful people made him their king, but soon after he was killed to settle a family score.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books